2014
DOI: 10.1016/j.jaac.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Cognitive-Behavioral Therapy for Adolescents With Obsessive-Compulsive Disorder: A Randomized Controlled Non-inferiority Trial

Abstract: ObjectiveMany adolescents with obsessive-compulsive disorder (OCD) do not have access to evidence-based treatment. A randomized controlled non-inferiority trial was conducted in a specialist OCD clinic to evaluate the effectiveness of telephone cognitive-behavioral therapy (TCBT) for adolescents with OCD compared to standard clinic-based, face-to-face CBT.MethodSeventy-two adolescents, aged 11 through 18 years with primary OCD, and their parents were randomized to receive specialist TCBT or CBT. The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 42 publications
3
116
0
1
Order By: Relevance
“…49 In recent years, research has begun to focus on developing evidence-based methods for increasing the availability of, and access to, CBT. Novel approaches that have shown promise include CBT delivered via telephone 50 or web-camera 51 and internet CBT with minimal therapist input. 52 While further validation is required, these methods have the potential to transform service delivery for this population.…”
Section: Future Directionsmentioning
confidence: 99%
“…49 In recent years, research has begun to focus on developing evidence-based methods for increasing the availability of, and access to, CBT. Novel approaches that have shown promise include CBT delivered via telephone 50 or web-camera 51 and internet CBT with minimal therapist input. 52 While further validation is required, these methods have the potential to transform service delivery for this population.…”
Section: Future Directionsmentioning
confidence: 99%
“…Further details: students screening positive for depression in a web-based screening tool were invited to take part in telepsychiatric consultation 311 Turner et al 309 compared telephone CBT to face-to-face CBT. They found no significant clinical difference between the two groups following treatment after assessing the groups with a number of clinical scales, indicating the non-inferiority of telephone CBT compared with face to face.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Turner, 2014, UK 309 Clinical outcome: no significant difference, tCBT non-inferior to CBT. Clinician-rated global functioning -no significant difference…”
Section: Activity 2: Project Months 22 and 23mentioning
confidence: 99%
“…At least one uncontrolled feasibility study also exists [98]. A non-inferiority RCT comparing telephone-delivered CBT with standard in-office CBT showed that CBT could be effectively delivered over the telephone [99].…”
Section: Modified Cbtmentioning
confidence: 99%